2021
DOI: 10.1038/s41398-021-01671-6
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence of suicidal ideation and suicide plan among people with schizophrenia: a meta-analysis and systematic review of epidemiological surveys

Abstract: Schizophrenia is a severe psychiatric disorder with high premature mortality rates. This is a meta-analysis and systematic review of the prevalence of suicidal ideation (SI) and suicide plan (SP) among people with schizophrenia. PubMed, Web of Science, Embase, and PsycINFO were systematically searched from their respective inception to October 10, 2020. Data on prevalence of SI and/or SP were synthesized using the random effects model. Twenty-six studies covering 5079 people with schizophrenia were included fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 83 publications
3
46
1
3
Order By: Relevance
“…Suicidal ideation, plans and previous attempts, are as common as 27.7% in outpatients with schizophrenia, and are the strongest predictors of completed suicide [ 92 ]. Recognizing suicidal risk factors in schizophrenia is extremely important in suicidal risk assessment, and in this regard a suicide risk formulation has been recently proposed, comprising risk status, risk state, available resources and foreseeable events [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal ideation, plans and previous attempts, are as common as 27.7% in outpatients with schizophrenia, and are the strongest predictors of completed suicide [ 92 ]. Recognizing suicidal risk factors in schizophrenia is extremely important in suicidal risk assessment, and in this regard a suicide risk formulation has been recently proposed, comprising risk status, risk state, available resources and foreseeable events [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…At this point, the comparison of the data we obtained from the study with the studies in the literature investigating the prevalence of suicidal behavior in patients with schizophrenia can be a guide in understanding whether the pandemic period creates an additional negativity. In a recent meta-analysis in patients with schizophrenia, lifetime and point prevalence of suicide thoughts were 34.5% and 29.9%, respectively ( Bai et al, 2021 ). Tourino et al also reported that 1-year prevalence of suicide thoughts was 16.2% in these patients ( Tourino et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is associated with suicidal ideation[ 38 ]. In the United Kingdom, intentional paracetamol overdose is the most frequent cause of ALF.…”
Section: Acute Liver Failurementioning
confidence: 99%